Prognostic Value of Echocardiography in Hypertensive Versus Nonhypertensive Participants From the General Population. Issue 4 (April 2018) - Modin, Daniel; Biering-Sørensen, Sofie Reumert; Mogelvang, Rasmus; Landler, Nino; Jensen, Jan Skov; Biering-Sørensen, Tor
Abstract : Hypertension may be the most significant cardiovascular risk factor. Few studies have assessed the prognostic value of echocardiography in hypertensive individuals. This study examines the incremental prognostic value of adding echocardiographic parameters to established risk factors in individuals from the general population with and without hypertension. A total of 1294 individuals from the general population underwent a health examination and an echocardiogram including 2-dimensional speckle tracking. Outcome was a composite of ischemic heart disease and heart failure. The prevalence of hypertension was 38.3%. During a median follow-up of 12.5 years (interquartile range, 9.4–12.8 years), 222 participants (17.2%) developed the outcome. Out of these 222 events, 145 (65%) occurred in hypertensive participants, whereas 77 (35%) occurred in nonhypertensive individuals, corresponding to an incidence rate of 32/(1000×person-years) and 8/(1000×person-years), respectively. Follow-up was 100%. After multivariable adjustment, only left ventricular mass index predicted the outcome in hypertensive individuals, whereas only global longitudinal strain predicted the outcome in nonhypertensive individuals. In hypertensive individuals the prognostic value of left ventricular mass index was incremental to SCORE and abnormal ECG status. In nonhypertensive individuals the prognostic value of global longitudinal strain was incremental to SCORE and abnormal ECG status. The prognostic value of echocardiography in predicting cardiovascular outcomes in the general population is altered by hypertension. In hypertensive individuals, left ventricular mass index added incremental prognostic value in addition to established risk factors. In nonhypertensive individuals, global longitudinal strain added incremental prognostic value in addition to established risk factors. Abstract : Supplemental Digital Content is available in the text.